2018
DOI: 10.3892/etm.2018.6981
|View full text |Cite
|
Sign up to set email alerts
|

In�vivo confocal laser scanning microscopy imaging of skin inflammation: Clinical applications and research directions (Review)

Abstract: In vivo confocal laser scanning microscopy (CLSM) is a novel imaging technique that provides noninvasive, morphological characterization of skin structures with a resolution that is very close to that of light microscopy. Moreover, as it allows repeated imaging of the same skin area at different time-points, it is an excellent method for monitoring disease course, response to treatment or specific stimuli and a path to study dynamic phenomena in real-time. To date, two different variants of in vivo CLSM have b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
41
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(41 citation statements)
references
References 51 publications
(70 reference statements)
0
41
0
Order By: Relevance
“…Skin ageing can be due to natural processes occurred, intensified or accumulated in time (chronological, intrinsic or natural ageing) or upon solar radiation exposure (extrinsic, photo-ageing). Changes in the dermal layer of the skin, alteration and modifications of the extracellular matrix, as well as increased inflammatory markers and decreased blood flow lead to aging skin (18)(19)(20).…”
Section: Skin Ageing -Natural Occurrence and External Triggersmentioning
confidence: 99%
“…Skin ageing can be due to natural processes occurred, intensified or accumulated in time (chronological, intrinsic or natural ageing) or upon solar radiation exposure (extrinsic, photo-ageing). Changes in the dermal layer of the skin, alteration and modifications of the extracellular matrix, as well as increased inflammatory markers and decreased blood flow lead to aging skin (18)(19)(20).…”
Section: Skin Ageing -Natural Occurrence and External Triggersmentioning
confidence: 99%
“…It has been observed that microvascular endothelial dysfunction has as substrate the appearance of anti-endothelial antibodies and, mainly, the presence of anti-intercellular adhesion molecule (ICAM)-1 antibodies (6). Activated endothelial cells release proinflammatory cytokines and connective tissue growth factors, interleukin (IL)-1, IL-4, tumor necrosis factor (TNF)-α, IL-6 and IL-8 transforming growth factor (TGF)-β, which induce aberrant hyperactivated fibroblasts (7)(8)(9)(10)(11). Early endothelial cell involvement in SSc, leads to the destruction of blood capillaries with reduction in microvasculature through vascular repair and defective neoangiogenesis simultaneously with impaired lymphatic circulation followed by exudative accumulation and edema formation.…”
Section: Introductionmentioning
confidence: 99%
“…Imaging techniques are also used to assess non-invasive skin changes in psoriasis or high performance liquid chromatography or cell membrane fluidity; however, this study aimed to evaluate only the inflammatory activity (24)(25)(26)(27).…”
Section: Discussionmentioning
confidence: 99%